The effect of Dodonaea viscosa var. angustifolia on oral pathogens - Naidoo, Roxanne (My University, 2012)
Dental caries and periodontal diseases are the most common bacterial oral infections in humans. Prevention and treatment of these infections are oral hygiene measures including antimicrobial compounds which can be chemical agents or natural products. Dodonaea viscosa var. angustifolia is an indigenous South African plant that has antibacterial, antiviral and anticandida properties. This study investigated the antibacterial and antivirulence effect of D. viscosa var. angustifolia on cariogenic bacteria and the causative organisms of periodontal diseases.
Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Medicine. Johannesburg 2012.
Keywords: Plants, Medicinal--therapeutic use; Plants, Medicinal--South Africa; Dental Caries--prevention & control; Periodontal Diseases--prevention & control.